1997
DOI: 10.1002/(sici)1097-0231(199709)11:14<1493::aid-rcm40>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of oligosaccharide composition and structure by quadrupole ion trap mass spectrometry

Abstract: The use of electrospray ionization-quadrupole ion trap mass spectrometry for the characterization of linear oligosaccharides and N-linked protein oligosaccharide mixtures is described. Tandem mass spectrometry (MS/MS) experiments with orders higher than two offer a number of ways to enhance MS/MS spectra and to derive information not present in MS and MS2 spectra. Three such methods are presented in this paper. (a) Collisional activation of permethylated oligosaccharide molecular ions (MS2) as illustrated by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
82
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 27 publications
0
82
1
Order By: Relevance
“…6 In both cases, however, the product structures remain to be characterized. A large body of work has shown that spectral comparisons of isomers at different stages of sequential molecular fragmentation (MS n ) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] are clearly different, although in one case, reproducibility has been reported to be "vague". 25 In our experience, spectral reproducibility has been excellent, 26 and this very feature has provided an opportunity to build a searchable fragment library 27 and derive glycan structure with supporting tools.…”
mentioning
confidence: 99%
“…6 In both cases, however, the product structures remain to be characterized. A large body of work has shown that spectral comparisons of isomers at different stages of sequential molecular fragmentation (MS n ) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] are clearly different, although in one case, reproducibility has been reported to be "vague". 25 In our experience, spectral reproducibility has been excellent, 26 and this very feature has provided an opportunity to build a searchable fragment library 27 and derive glycan structure with supporting tools.…”
mentioning
confidence: 99%
“…Different combinations of ionization techniques, ion activation, and mass analyzers have been used, including fast atom bombardment (FAB)-MS [10 -12], infrared-laser desorption MS [13,14], matrix-assisted laser desorption/ionization (MALDI)/magnetic sector MS [15][16][17], electrospray ionization (ESI)-MS [18,19], MALDI/time-offlight (TOF)-MS [20 -22], ESI ion-trap MS [23][24][25], MALDI Fourier transform MS [26], ESI-or MALDIbased quadrupole/TOF-MS [27][28][29][30], MALDI/Postsource Decay (PSD) TOF-MS [31][32][33], and, more recently, MALDI-TOF/TOF-MS [34 -38].…”
mentioning
confidence: 99%
“…TOF/TOF or Q-TOF mass spectrometers have been widely used in tandem MS characterization of oligosaccharides. In contrast to such tandem-in-space types of instruments, where tandem MS is limited to a MS 2 stage (not including in-source fragmentation), ion storage devices, such as ion trap mass spectrometers, allow multi-stage activations of the parent oligosaccharide ions into successive fragment ions [13,[47][48][49]. Sequential fragmentation, analogous to successive enzyme treatment in the classic sequencing technique, is thus possible with ion trap instruments.…”
mentioning
confidence: 99%